PERBEDAAN ADAPTASI HOSPITALISASI SEBELUM DAN SESUDAH DIBERIKAN BIBLIOTHERAPY PADA ANAK USIA PRASEKOLAH DIRUANG IRNA E RSUD SYAMRABU BANGKALAN 1 - M.Kep, Mufarika (NHM PRESS, 2085)
Maladaptive behavior that occurs in preschool children in hospitalization is torefuse to eating, often asking, crying slowly, uncooperative to health workers, so the hospitalcare becomes loss of control and activity limitation. . Based on the preliminary study, from10 students there was 1 child can adapt well, 8 children can adapt to enough category and 1child adapt to less category. The objectives of the study was to analyze the difference ofadaptation of hospitalization before and after being given Bibliotherapy in preschoolchildren in room Irna E RSUD Syamrabu Bangkalan. This research used the Pre Experimental design with One Group Pretest Posttestapproach. Independent variable that was Bibliotherapy and dependent variable wasadaptation of hospitalization. The study population was 20 children based on the average ofhospitalized patients each month in 2017 and 10 respondents used Systematic RandomSampling technique. The instrument used for Bibliotherapy therapy is storybook, and it wasby analyzed using Paired t-test. Based on the result of statistical test with pairet t-test, the result was ? Value: 0,000<?: 0,05 so that Ha was accepted, it means there was difference on adaptation before andafter Bibliotherapy of preschool children's in Irna E Room of Syamrabu Bangkalan Hospital. Nurses may apply Bibliotherapy to improve adaptation of child hospitalizationduring hospitalization. In addition it is also recommended to involve parents in the provisionof Bibliotherapy with the aim that parents can also intervene independently.